Proposal for an instrument to measure identity from urban furniture - Paredes de la Rosa, Beatriz (UNIVERSIDAD DE SONORA, 2021)
Urban identity is a recurring theme within urban design as it defines the connection of a human group with its environment and the level of roots present in a neighborhood or city. A public space where the inserts that are designed, the urban furniture in this case, then contribute to fostering that sense of belonging would then be the maxim in urban design. But how should furniture be designed for this purpose? What factors are involved in the process? What should be the strategies to follow? How could you know if an urban element fosters identity? Due to these and other questions, it was believed necessary to create an instrument that helps to measure the degree of belonging and therefore to identify significant interactions in subject-object relationships. All of the aforementioned is studied under a holistic approach where systems thinking helps to minimize reductionist views.